Improving QoS Of WiMAX By ondemand bandwidth allocation based on PMP mode - Sun, Zhen Tao; Gani, Abdullah; Sun, Xiu Ying; Liu, Ning (Academy Publisher, 2011)
The bandwidth allocation in both wired and wireless networks has posed great challenges to network engineers for improving desirable Quality of Service (QoS), Bandwidth allocation is always an important element for improve QoS of network. Despite this, IEEE 802.16e-2005 does not have a bandwidth allocation algorithm or mechanism to support (worldwide interoperability for microwave access) WiMAX network presently. This includes both uplink (UL) and downlink (DL) directions. Thus, most of researches are focusing in this area. In order to improve the QoS of WiMAX demand, the total capacity of WiMAX system must be optimized. Thereby, in this research, a new bandwidth allocation mechanism for WiMAX network is proposed, called On Demand Bandwidth Allocation (ODBA). The proposed mechanism design has the management module in the Subscribe Station (SS), which is for management UL bandwidth, and one new module in the Base Station (BS). This includes UL/DL bandwidth allocation and service flow schedule. We tested the new mechanism by running in the simulation of OMNET++. As the results show that the ODBA mechanism has improve the scheduled probability (SP) and increase the throughput of WiMAX network.